Admission Serum Ionized and Total Calcium as New Predictors of Mortality in Patients with Cardiogenic Shock. (8th April 2021) - Yu, Yue; Yu, Jingwen; Yao, Renqi; Wang, Pei; Zhang, Yufeng; Xiao, Jian; Wang, Zhinong
Abstract : Background . Although serum calcium has been proven to be a predictor of mortality in a wide range of diseases, its prognostic value in critically ill patients with cardiogenic shock (CS) remains unknown. This retrospective observational study is aimed at investigating the association of admission calcium with mortality among CS patients. Methods . Critically ill patients diagnosed with CS in the Medical Information Mart for Intensive Care-III (MIMIC-III) database were included in our study. The study endpoints included 30-day, 90-day, and 365-day all-cause mortalities. First, admission serum ionized calcium (iCa) and total calcium (tCa) levels were analyzed as continuous variables using restricted cubic spline Cox regression models to evaluate the possible nonlinear relationship between serum calcium and mortality. Second, patients with CS were assigned to four groups according to the quartiles (Q1-Q4) of serum iCa and tCa levels, respectively. In addition, multivariable Cox regression analyses were used to assess the independent association of the quartiles of iCa and tCa with clinical outcomes. Results . A total of 921 patients hospitalized with CS were enrolled in this study. A nonlinear relationship between serum calcium levels and 30-day mortality was observed (all P values for nonlinear trend < 0.001 ). Furthermore, multivariable Cox analysis showed that compared with the reference quartile (Q3: 1.11 ≤ iCa < 1.17   mmol / L ), the lowest serum iCa level quartile (Q1: iCa < 1.04   mmol / L ) was independently associated with an increased risk of 30-day mortality (Q1 vs. Q3: HR 1.35, 95% CI 1.00-1.83, P = 0.049 ), 90-day mortality (Q1 vs. Q3: HR 1.36, 95% CI 1.03-1.80, P = 0.030 ), and 365-day mortality (Q1 vs. Q3: HR 1.28, 95% CI 1.01-1.67, P = 0.046 ) in patients with CS. Conclusions . Lower serum iCa levels on admission were potential predictors of an increased risk of mortality in critically ill patients with CS.